Triazoles and Their Derivatives: Chemistry, Synthesis, and Therapeutic Applications - Matin, Mohammed M.; Matin, Priyanka; Rahman, Md. Rezaur; Ben Hadda, Taibi; Almalki, Faisal A.; Mahmud, Shafi; Ghoneim, Mohammed M.; Alruwaily, Maha; Alshehri, Sultan (Frontiers in Molecular Biosciences, 2022)
Amongst the nitrogen-containing heterocyclic compounds, triazoles emerge with superior pharmacological applications. Structurally there are two types of five-membered triazoles: 1,2,3-triazole and 1,2,4-triazole. Due to the structural characteristics both 1,2,3- and 1,2,4-triazoles are able to accommodate a broad range of substituents (electrophiles and nucleophiles) around the core structures and pave the way for the construction of diverse novel bioactive molecules. Both the triazoles and their derivatives have significant biological properties including antimicrobial, antiviral, antitubercular, anticancer, anticonvulsant, analgesic, antioxidant, anti-inflammatory, and antidepressant activities. These are also important in organocatalysis, agrochemicals, and materials science. Thus, they have a broad range of therapeutic applications with ever-widening future scope across scientific disciplines. However, adverse events like hepatotoxicity and hormonal problems lead to a careful revision of the azole family to get higher efficacy with minimum side effects. This review focuses on the structural features, synthesis, and notable therapeutic applications of triazoles and related compounds.